PERANAN SUMBER DAYA MANUSIA DALAM MENINGKATKAN PEMBANGUNAN MASYARAKAT DI DESA UMBANUME KECAMATAN PIRIME KABUPATEN LANNY JAYA - Wakerkwa, Onius (HOLISTIK, Journal Of Social and Culture, 2016)
Human resources development can be seen from two aspects formal education and non-formal. Human resources that develops or forward even say will can contribute to the community development. The government of Kecamatan Pirime, especially Umbanume village encourage people to improve education good formal and non-formal to accelerate the development of any individuals and families. From reality is that man is will determine the ability of the community in a village to develop himself, although in the village is in its natural resources. Such things this is what is one of them are in the land of Papua, where natural resources which is abundant, but yet to be in full by the community Papua itself, so that other group which should enjoy the result of natural resources on in the land of Papua. The participation of the Umbanume village still at a low rate to moderate. Human resources affect public participation in the Umbanume village, it means the higher education someone so the higher the level of participation. Keywords: development, human resources, participation